Observation of topological edge states induced solely by non-Hermiticity in an acoustic crystal - Gao, He (2022)
Non-Hermiticity alters band topology in the presence of loss and/or gain in topological systems, which not only introduces new definitions in topological classifications, topological invariants, and the bulk-boundary correspondence, but also gives rise to unprecedented applications such as topological insulator lasers. Most existing non-Hermitian topological systems derive their topological phases from Hermitian components, rather than being driven by non-Hermiticity itself. Here we report on the experimental observation of topological edge states induced solely by non-Hermiticity in an acoustic crystal. The acoustic crystal consists of a periodic one-dimensional chain of coupled acoustic resonators with tunable loss. In the Hermitian limit, or when the loss is negligible, the crystal exhibits no band gap and hosts no topological edge states. By introducing loss, we show that a band gap is induced, which can be either topological or trivial, depending on the loss configuration. In the topological case, topological edge modes are found inside the band gap. These results demonstrate that non-Hermiticity is able to drive a topological phase transition from a trivial system to a topological one, offering the possibilities for actively steerable topological wave manipulations in applications ranging from acoustics to photonics.